STRATEGI PENGELOLAAN LIMBAH KONSTRUKSI BERBASIS KONSTRUKSI BERKELANJUTAN : SYSTEMATIC LITERATURE REVIEWSTRATEGI PENGELOLAAN LIMBAH KONSTRUKSI BERBASIS KONSTRUKSI BERKELANJUTAN : SYSTEMATIC LITERATURE REVIEW: STRATEGI PENGELOLAAN LIMBAH KONSTRUKSI BERBASIS KONSTRUKSI BERKELANJUTAN : SYSTEMATIC LITERATURE REVIEW - Faluth Syifa; Muhammad Dwi Bayu; Pungky Dharma Saputra (Construction and Material Journal, 2026)
Construction waste management is a crucial issue in the construction industry, especially in Indonesia, which faces challenges in the reduction, reutilization, and recycling of building materials. Poorly managed construction waste can negatively impact the environment and project efficiency. Therefore, a comprehensive review of effective and sustainable construction waste management strategies is required. This research aims to identify, analyze, and summarize various approaches in construction waste management through the Systematic Literature Review (SLR) method. This method is used to systematically review relevant previous research results, so as to provide a comprehensive overview of the trends, challenges, and solutions that have been implemented in construction waste management. In this study, data was obtained from a review of 100 scientific journals that discuss construction waste and demolition waste management. The results showed that technology-based approaches, government policies, and the application of circular economy principles are the main factors in reducing the environmental impact of construction waste. In addition, collaboration between stakeholders, such as contractors, government, and communities, also plays an important role in the effectiveness of waste management. The findings of this study have significant implications for the development of sustainable construction policies and practices in Indonesia. It is hoped that the results of this study can serve as a basis for more effective decision-making in managing construction waste as well as encourage innovation in the recycling and reutilization system of building materials.